Testing of Non-Specific Parameters of Butterfly Pea Flower Cultivation from Cipangeran Village, Saguling District, West Bandung Regency - Rumaseuw, Ellen Stephanie; Saptiningsih, Monica (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The blue butterfly pea flower (Clitoria ternatea) is a medicinal plant rich in bioactive compounds, including anthocyanins and flavonoids, with health benefits and potential in the food and cosmetics industries. There has been no scientific study on the non-specific parameters of cultivated butterfly pea flowers and their simple quality related to the environmental conditions in the village. Standardization of non-specific parameters, such as moisture content, ash content, and microbial contamination, is crucial to ensure the quality and safety of butterfly pea-based products. This research aims to analyze the non-specific parameters of butterfly pea in support of developing quality standards suitable for the pharmaceutical and cosmetic industries. The research method uses experimental techniques, starting with sample collection, laboratory analysis, and data analysis. The results of the water-soluble ash test, 99.63% indicate contamination by inorganic compounds that dissolve in water, while the acid-insoluble ash content of 0.09% suggests minimal contamination by silica. The water-soluble extract content of 54.98% and the ethanol-soluble extract content of 99.98% indicate the solubility of compounds in solvents, which are important for the extraction and formulation of traditional medicine products or herbal products that use water and ethanol as solvents. In conclusion, the results of non-specific parameter tests on the blue butterfly pea flower simplicia from Cipangeran Village indicate that the simplicia has excellent physicochemical qualities.